Predictors and Prognostic Effects of Perioperative Myocardial Injury After Transcatheter Aortic Valve Replacement According to VARC-3 Criteria - Hu X; Zhao Z; Wang C; Feng D; Chen Y; Niu G; Zhou Z; Zhang H; Li Z; Ye Y; Wang M; Wu Y (Clinical Interventions in Aging)
Xiangming Hu,1,* Zhenyan Zhao,1,* Can Wang,1,* Dejing Feng,1 Yang Chen,2 Guannan Niu,1 Zheng Zhou,1 Hongliang Zhang,1 Zhe Li,1 Yunqing Ye,1 Moyang Wang,1 Yongjian Wu1 1Department of Cardiology, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Cardiology, Peking University People’s Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Moyang Wang; Yongjian Wu, Department of Cardiology, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100037, People’s Republic of China, Email wangmoyang1983@vip.sina.com; fuwaiwyj@163.comPurpose: The impact of periprocedural myocardial injury (PPMI) according to VARC-3 criteria in patients undergoing transcatheter aortic valve replacement (TAVR) remains unclear. This study aimed to investigate the incidence, risk factors, and prognosis of PPMI in patients with severe aortic who underwent TAVR in China.Materials and Methods: Between September 2012 and November 2021, 516 patients with severe aortic stenosis who underwent TAVR at the Fuwai Hospital were consecutively enrolled. PPMI was defined according to the VARC-3 criteria as a 70-fold increase of upper reference limit in cardiac troponin I (cTnI) levels. We compared the baseline characteristics, perioperative conditions, and in-hospital and long-term endpoints between the PPMI and non-PPMI groups. Logistic regression analysis was used to determine the predictors of PPMI. Survival probabilities for outcomes between the PPMI and non-PPMI groups were estimated using the Kaplan-Meier method.Results: Of the enrolled patients (mean age: 75.5± 7.2 years, 57.5% male), the incidence of PPMI was 20.5%. The median cTnI was 24.9 (interquartile range: 11.4− 60.2) times the upper reference limit. After multivariable adjustment, female sex (odds ratio [OR]: 3.01, 95% confidence interval [CI]: 1.88− 4.82, P < 0.001), anticoagulant use (OR: 0.27, 95% CI: 0.08− 0.96, P = 0.043), balloon-expandable valve (OR: 0.27, 95% CI: 0.09− 0.79, P = 0.017), and secondary valve implantation (OR: 2.66, 95% CI: 1.40− 5.03, P = 0.003) were significantly associated with PPMI. Patients with PPMI had short- and long-term outcomes similar to those without PPMI.Conclusion: Female sex and secondary valve implantation are predictors of an increased risk of PPMI, whereas baseline anticoagulant use and the use of balloon-expandable valves are protective factors. The presence of PPMI does not seem to indicate poor short- or long-term prognosis in patients undergoing TAVR.Keywords: aortic stenosis, transcatheter aortic valve replacement, myocardial injury, risk factor, prognosis